The opportunity for coupling of sugar mill and paper mill through an effective and efficient use of energy - Sri Hardina Noviati; Mohanty, B.; Mora, Jean-Claude; Edelman, David J.; Bo, Khin; Netherland - DSO Pwg. (Bangkok : Asian Institute of Technology, 1991)
Bagasse, the by-product of . sugar industry is a potential raw material for pulp and paper industry. It is also utilised as fuel to satisfy all the heat and power demand of the s"ugar industry. Energy conservation opportunities have been explored. In the sugar mill with the main aim to save bagasse, so that it can be sold as raw material or consumed as fuel to produce electricity that can be sold. The measures studied include better thermal cascades using MVR, ejecto-compressor and higher steam generation. In the paper mill, employing MVR and cogeneration system are considered to reduce its energy intensity. Various scen arios have been considered to assess the economic consequences of the different technical options by considering the opportunity of coupling the sugar mill with the paper mill. When the sugar mill sells bagasse to the paper mill, the best option for the new sugar mill and paper mill is adopting cogeneration system at 40 bar in Thailand and 80 bar in Indonesia, for which pay-back periods are found to be 8. 8 years and 3.7 years respectively for the sugar mill, 8.6 years and 5.5 years for the paper mill. However the existing bagasse price does not encourage the sugar mill in Thailand to sell bagasse. It is more attractive to store and burn bagasse during off-season and sell electricity to the paper mill. The pay-back periods in this case are 7.6 years and 7.8 years when adopting the cogeneration system at 40 bar and 80 bar respectively.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Sugar factories -- Energy conservation; Paper mills -- Energy conservation